Preparation method of amorphous nanocrystalline magnetic core of DBI type low-voltage current transformer and magnetic core

By smelting and rapidly solidifying metal materials under an inert atmosphere, combining annealing and magnetic field treatment, amorphous nanocrystalline magnetic core of DBI type low-voltage current transformer was prepared, which solved the problems of low efficiency and poor stability of traditional magnetic cores and achieved uniform magnetic field Distribution and performance improvements.

CN119181581AInactive Publication Date: 2024-12-24STATE GRID SHANDONG ELECTRIC POWER CO MARKETING SERVICE CENT (MEASURING CENT)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411360407.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional magnetic cores generate hysteresis loss, eddy current loss and residual loss under alternating magnetic fields, resulting in reduced efficiency and rapid deterioration in DC biased state. The performance stability of amorphous nanocrystalline magnetic cores is subject to grain size and crystalline. The grid structure has a great influence.

Method used

The amorphous nanocrystalline magnetic core preparation method of DBI type low-voltage current transformer is adopted to quickly solidify and form an amorphous alloy structure by melting metal materials and additives under an inert atmosphere, and form an amorphous nanocrystalline alloy structure through annealing treatment, combining with magnetic field Annealing treatment to prepare a magnetic core with a uniform magnetic field distribution.

Benefits of technology

The magnetic field on the surface of the magnetic core is uniformly distributed for a longer time, reducing hysteresis loss, improving magnetic permeability and magnetic saturation magnetic induction strength, enhancing material stability and magnetic properties, and optimizing the wide range performance and production efficiency of the magnetic core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181581A_ABST
    Figure CN119181581A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of amorphous and nanocrystalline magnetic cores, and provides a preparation method of a DBI type low-voltage current transformer amorphous and nanocrystalline magnetic core and the magnetic core. The preparation method of the amorphous nanocrystalline magnetic core of the DBI type low-voltage current transformer comprises the following steps: putting a metal material and an additive into a smelting furnace according to a set mass fraction ratio, and smelting at a set temperature in an inert atmosphere to obtain a uniform alloy liquid; the uniform alloy liquid is rapidly cooled through a rapid solidification method, and an amorphous alloy structure is formed; the amorphous alloy structure is subjected to annealing treatment, and by controlling the temperature and time in the annealing treatment process, part of the amorphous alloy structure forms an amorphous nanocrystalline alloy structure; and the amorphous nanocrystalline alloy structure is formed and processed, annealing treatment is conducted again, and the magnetic core with the needed shape and size is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of amorphous nanocrystalline magnetic cores, and in particular relates to a method for preparing an amorphous nanocrystalline magnetic core of a DBI type low-voltage current transformer and a magnetic core. Background Art

[0002] The statements in this section merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] For DBI mutual inductors, the magnetic core is the core material of the mutual inductor. When the mutual inductor is working, an alternating magnetic field is generated in the magnetic core, thereby generating constantly changing magnetic lines of force. Traditional magnetic cores use ferromagnetic materials, which produce hysteresis loss, eddy current loss and residual loss under the alternating magnetic field, which reduces the efficiency of the device and increases energy consumption. At the same time, when traditional devices work in a DC bias state, the ferromagnetic core is quickly magnetized and saturated, and the performance deteriorates rapidly, causing component failure. Amorphous nanocrystalline magnetic cores have excellent properties such as high saturation magnetic induction intensity and low hysteresis, and are widely used in power transformers, electronic equipment and other fields. However, its performance stability is greatly affected by factors such as grain size and lattice structure, and traditional preparation methods have problems such as grain growth and unstable lattice structure. Summary of the invention

[0004] In order to solve the technical problems existing in the above-mentioned background technology, the present invention provides a method for preparing a DBI (anti-DC Bias) type low-voltage current transformer amorphous nanocrystalline magnetic core and a magnetic core, which can maintain a uniform distribution of the magnetic field on the surface of the magnetic core for a longer time, reduce hysteresis loss, and improve wide-range performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A first aspect of the present invention provides a method for preparing an amorphous nanocrystalline magnetic core of a DBI type low voltage current transformer.

[0007] A method for preparing an amorphous nanocrystalline magnetic core of a DBI type low-voltage current transformer, comprising:

[0008] Put the metal material and additives into the furnace according to the set mass fraction ratio, and melt them at the set temperature under an inert atmosphere to obtain a uniform alloy liquid;

[0009] The uniform alloy liquid is rapidly cooled by a rapid solidification method to form an amorphous alloy structure;

[0010] Annealing the amorphous alloy structure, and controlling the temperature and time during the annealing process so that part of the amorphous alloy structure forms an amorphous nanocrystalline alloy structure;

[0011] The amorphous nanocrystalline alloy structure is formed and processed, and then annealed to prepare a magnetic core of a desired shape and size.

[0012] As an implementation method, a magnetic field is applied during the re-annealing process.

[0013] As an implementation method, the calculation formula of the applied magnetic field strength B is:

[0014]

[0015] Among them, B_s is the saturation magnetic induction intensity, H represents the intensity of the external magnetic field, and H_c represents the critical magnetic field of the material.

[0016] As an implementation mode, before the annealing treatment is performed again, the surface of the magnetic core formed by the amorphous nanocrystalline alloy structure is plated.

[0017] As an embodiment, the metal material is iron; the additives include silicon, cobalt and niobium; the mass fraction ratio of the metal material and the additives is: iron: 75%-80%; silicon: 10%-15%; cobalt: 5%-10%; niobium: 1%-3%.

[0018] As an embodiment, the additive further comprises: a surfactant, a stabilizer, a flux, a grain boundary strengthener, and an oxidant;

[0019] The mass fraction of the surfactant is 0.1%-2%; the mass fraction of the stabilizer is 0.1%-5%; the mass fraction of the flux is 0.1%-2%; the mass fraction of the grain boundary strengthener is 0.1%-3%; and the mass fraction of the oxidant is 0.1%-1%.

[0020] As an embodiment, the temperature during the annealing process is controlled within the range of 300° C. to 350° C., and the time during the annealing process is controlled within the range of 5 to 15 hours.

[0021] As an implementation method, the formula for determining the annealing time is:

[0022]

[0023] Wherein, t is the annealing time, V is the volume of the amorphous nanocrystalline core, D is the thermal diffusion coefficient of the material, A is the surface area of ​​the material, E is the activation energy of the annealing process, R is the gas constant, T is the temperature, k, m, and n are empirical constants used to adjust the degree of influence of each term in the formula.

[0024] As an implementation method, the formula for determining the annealing time is:

[0025]

[0026] Where T is the annealing temperature, V is the volume of the amorphous nanocrystalline core, E is the activation energy of the annealing process, K is the Boltzmann constant, and a, b, and p are empirical constants.

[0027] A second aspect of the present invention provides a magnetic core.

[0028] A magnetic core is prepared by using the steps in the above-mentioned method for preparing an amorphous nanocrystalline magnetic core of a DBI type low-voltage current transformer.

[0029] The beneficial effects of the present invention are:

[0030] The method for preparing a wide-range DBI type low-voltage current transformer amorphous nanocrystalline core of the present invention has at least the following effects:

[0031] (1) After the present invention anneals the amorphous alloy structure, the magnetic field annealing is used for the formed magnetic core to selectively adjust the microstructure of the amorphous nanocrystalline magnetic core. Through appropriate annealing, some internal stresses and defects can be eliminated, and the crystallinity and stability of the material can be improved. Magnetic field annealing can perform directional processing on the material at the magnetic domain level and adjust the magnetic properties.

[0032] (2) The present invention utilizes magnetic field annealing to make the material have stronger magnetism in a specific direction, improve the magnetic properties of the magnetic core such as magnetic permeability and magnetic saturation magnetic induction intensity, thereby improving the magnetic energy storage density and magnetic induction intensity of the magnetic core.

[0033] (3) The annealing time and temperature of the present invention and the magnetic field strength of the magnetic field annealing can be controlled. By changing the parameters of annealing and magnetic field annealing, such as temperature, time and magnetic field strength, the microstructure and magnetic properties of the material can be precisely controlled, thereby optimizing and customizing the performance of the magnetic core.

[0034] (4) By adopting this composite annealing technology, the magnetic core material can be processed in a relatively short time, thereby improving production efficiency and process stability and reducing preparation costs.

[0035] (5) Magnetic field homogenization treatment can make the magnetic field distribution inside the magnetic core more uniform and stable, reduce the influence of magnetic field gradient on the electroplating process, and help to obtain a more uniform and dense surface coating. Through magnetic field homogenization treatment, the magnetic field on the surface of the magnetic core can be made more uniform, thereby improving the adhesion between the surface and the coating and reducing the possibility of coating peeling. Uniform magnetic field distribution can reduce the local current density difference during the electroplating process, help to obtain a more uniform and dense coating structure, thereby improving the hardness, corrosion resistance and wear resistance of the coating.

[0036] Advantages of additional aspects of the present invention will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0038] Figure 1 It is a flow chart of a method for preparing an amorphous nanocrystalline magnetic core of a DBI type low voltage current transformer according to an embodiment of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0040] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0041] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0042] Because new energy has strong randomness, volatility and intermittency, after large-scale new energy is connected to the grid, the system will face multiple challenges in different time scales such as accurate measurement, stable control and operation. For example, in winter nights with abundant wind and summer days with abundant sunshine, wind turbines and solar cells are basically working at full load, while the power generation capacity is weak or the basic power is zero at other times, and the operating current of the transformer fluctuates greatly, far exceeding the measurement range of traditional current transformers (1% to 120% rated current). In both traditional power systems and new power systems, there are a large number of irregular electricity users such as seasonal electricity consumption, staged electricity consumption, daily electricity consumption, intermittent electricity consumption and uncertain electricity consumption, which makes the peak-to-valley difference of low-voltage power load continue to increase, and the working current variation range of low-voltage current transformers is getting wider and wider. At the same time, the uncertainty of the development of power consumption in residential and industrial user areas, the unpredictability of load changes in different periods, and the fast speed and large range of changes in power load, the peak-to-valley difference can reach more than 30 times, so that current transformers often work in low-load or overload states, resulting in inaccurate transformer measurement.

[0043] In addition, with the construction of new power systems, AC and DC transmission projects, new power consumption technologies and related power equipment have developed rapidly, and the proportion of DC transmission power in the entire power grid and the degree of interconnection between AC and DC power grids have increased year by year. On the load side, with the popularization and application of power electronics technology, the number of nonlinear loads connected to the power system has continued to increase, such as steel, petrochemical, ceramics, rail transit and other fields, resulting in a certain DC component in the load current; on the power supply side, the large-scale use of thyristors and frequency conversion equipment in photovoltaic new energy power generation will also produce a certain DC component. As a sensor device for detecting the power generation and consumption process in the power grid, the influence of DC components on the transformer cannot be ignored. Taking the current transformer as an example, in the case of DC components, the main magnetic flux will have a DC component, the DC magnetic flux and the AC magnetic flux are superimposed on each other, and the DC component is all used for excitation. Since the excitation characteristics of the iron core are nonlinear, with the increase of the DC component, the excitation current will present an asymmetric shape of the positive and negative half cycles, and a large number of harmonics will be generated, which will deteriorate the transmission characteristics of the current transformer, and eventually saturate the iron core, resulting in increased errors.

[0044] Figure 1 The flowchart of the method for preparing the amorphous nanocrystalline core of the DBI type low voltage current transformer according to the embodiment of the present invention is shown in FIG. Figure 1 , a method for preparing an amorphous nanocrystalline core of a DBI type low-voltage current transformer, comprising:

[0045] Step S101: placing metal materials and additives into a melting furnace according to a set mass fraction ratio, and melting them at a set temperature under an inert atmosphere to obtain a uniform alloy liquid.

[0046] In the specific implementation process, metal materials include iron, copper, etc., and additives such as boron, silicon, cobalt, niobium, etc.

[0047] For example, the metal material is iron; the additives include silicon, cobalt and niobium; the mass fraction ratio of the metal material and the additives is: iron: 75%-80%; silicon: 10%-15%; cobalt: 5%-10%; niobium: 1%-3%.

[0048] In other embodiments, the additives further include: a surfactant, a stabilizer, a flux, a grain boundary strengthener, and an oxidant;

[0049] The mass fraction of the surfactant is 0.1%-2%; the mass fraction of the stabilizer is 0.1%-5%; the mass fraction of the flux is 0.1%-2%; the mass fraction of the grain boundary strengthener is 0.1%-3%; and the mass fraction of the oxidant is 0.1%-1%.

[0050] Among them, surfactants, such as octylsilane, sulfonic acid, carboxylic acid, etc., are used to adjust the surface tension and fluidity of the alloy and help obtain a uniform alloy structure;

[0051] Stabilizers, such as zirconium, titanium and other elements, are used to prevent the alloy from undergoing phase change or precipitation during the preparation process and to improve its thermal and structural stability;

[0052] Fluxes, such as boron, phosphorus, lithium and other elements, are used to lower the melting point of the alloy and promote uniform mixing and rapid solidification of the alloy components;

[0053] Grain boundary strengtheners, such as silicon carbide, titanium carbide, aluminum oxide and other particles, are used to enhance the grain boundary strength and wear resistance of the alloy and improve its mechanical and magnetic properties;

[0054] Oxidants, such as iron oxide, cobalt oxide, nickel oxide, etc., are used to adjust the oxidation state of the alloy and control the lattice structure and magnetic properties.

[0055] Step S102: Rapidly cool the uniform alloy liquid through a rapid solidification method to form an amorphous alloy structure.

[0056] The rapid solidification method here includes a water-cooled copper wheel rapid solidification method or a laser rapid solidification method.

[0057] The water-cooled copper wheel rapid solidification method specifically includes:

[0058] First, the alloy material is heated to above the melting point to make it liquid. Then, the molten alloy is poured onto the surface of the rotating copper wheel. Since copper has good thermal conductivity, the alloy begins to cool rapidly the moment it comes into contact with the copper wheel.

[0059] Through rapid solidification, the atoms of the alloy do not have enough time to arrange into an ordered crystalline structure, but are "frozen" in a disordered amorphous structure; this amorphous structure has high hardness and excellent magnetic properties.

[0060] Step S103: performing annealing treatment on the amorphous alloy structure, and controlling the temperature and time during the annealing treatment process so that part of the amorphous alloy structure forms an amorphous nanocrystalline alloy structure.

[0061] Preferably, the temperature during the annealing process is controlled within the range of 300° C. to 350° C., and the time during the annealing process is controlled within the range of 5 to 15 hours. This temperature range can promote the transformation of the amorphous structure into a nanocrystalline structure, thereby improving the magnetic properties and mechanical properties.

[0062] In some optional embodiments, the annealing time is determined by the formula:

[0063]

[0064] Wherein, t is the annealing time, V is the volume of the amorphous nanocrystalline core, D is the thermal diffusion coefficient of the material, A is the surface area of ​​the material, E is the activation energy of the annealing process, R is the gas constant, T is the temperature, k, m, and n are empirical constants used to adjust the degree of influence of each term in the formula.

[0065] In some other optional embodiments, the formula for determining the annealing time is:

[0066]

[0067] Where T is the annealing temperature, V is the volume of the amorphous nanocrystalline core, E is the activation energy of the annealing process, K is the Boltzmann constant, and a, b, and p are empirical constants.

[0068] Step S104: the amorphous nanocrystalline alloy structure is subjected to forming processing (such as rolling, extrusion, etc.), and annealing treatment is performed again to prepare a magnetic core of a desired shape and size.

[0069] After annealing the amorphous alloy structure in this embodiment, the formed magnetic core is subjected to magnetic field annealing to selectively adjust the microstructure of the amorphous nanocrystalline magnetic core. Through appropriate annealing, some internal stresses and defects can be eliminated, and the crystallinity and stability of the material can be improved. In addition, magnetic field annealing can perform directional processing on the material at the magnetic domain level and adjust the magnetic properties.

[0070] In some embodiments, before the annealing treatment is performed again, the surface of the magnetic core formed by the amorphous nanocrystalline alloy structure is plated.

[0071] The surface coating of the magnetic core specifically includes:

[0072] Clean the surface of the core to remove grease, dust and other contaminants;

[0073] Apply a layer of adhesive on the surface of the cleaned magnetic core;

[0074] Place the magnetic core in the electroplating tank as the cathode. At the same time, place a nickel or chromium anode in the electroplating tank and apply current in a suitable electrolyte to deposit the metal ions on the anode on the surface of the magnetic core to form a coating.

[0075] After electroplating, the deposit is cleaned, dried and cured to improve its quality and durability.

[0076] In some embodiments, a magnetic field is applied during the re-annealing process.

[0077] Specifically, the re-annealing process is:

[0078] Clean the magnetic core that needs to be annealed to ensure that there is no contamination and oxide on the surface;

[0079] Apply an appropriate magnetic field near the magnetic core and determine the strength and direction of the magnetic field; the strength and direction of the magnetic field should be determined according to the specific requirements and material properties of the magnetic core;

[0080] Place the magnetic core in an annealing furnace and gradually heat it to the desired annealing temperature; during the heating process, ensure that an appropriate magnetic field is applied;

[0081] After reaching the annealing temperature, the core is kept in the annealing furnace for a period of time to ensure temperature uniformity and adjustment of the grain structure; during this process, the magnetic field is continuously applied;

[0082] Depending on the specific requirements, fast cooling or slow cooling can be selected; during the cooling process, the magnetic field continues to be applied until it is completely cooled. Applying a magnetic field during annealing can help adjust the magnetic properties, such as increasing the magnetic permeability or reducing the hysteresis loss.

[0083] The calculation formula of the applied magnetic field strength B is:

[0084]

[0085] Among them, B_s is the saturation magnetic induction intensity, H represents the intensity of the external magnetic field, and H_c represents the critical magnetic field of the material.

[0086] This embodiment can reduce unstable factors in the electroplating process through magnetic field homogenization treatment, improve the stability and controllability of the production process, and thus improve production efficiency. Since the quality and adhesion of the coating are improved, the coating peeling and defective rate are reduced, the maintenance cost and subsequent processing cost of the product can be reduced, saving production costs. At the same time, the coating can in turn more effectively maintain the uniformity of the magnetic field distribution of the magnetic core, thereby improving its wide-range performance. By first homogenizing the magnetic field and then coating, the magnetic field on the surface of the magnetic core can maintain a uniform distribution for a longer time, reducing hysteresis loss and improving wide-range performance.

[0087] In this embodiment, the annealing time and temperature and the magnetic field strength of the magnetic field annealing can be controlled. By changing the parameters of annealing and magnetic field annealing, such as temperature, time and magnetic field strength, the microstructure and magnetic properties of the material can be precisely controlled, thereby optimizing and customizing the performance of the magnetic core.

[0088] In one or more embodiments, a magnetic core is further provided, which is prepared using the steps in the method for preparing an amorphous nanocrystalline magnetic core of a DBI type low-voltage current transformer as described above.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing amorphous nanocrystalline core of DBI type low voltage current transformer, characterized in that: include: Put the metal material and additives into the furnace according to the set mass fraction ratio, and melt them at the set temperature under an inert atmosphere to obtain a uniform alloy liquid; The uniform alloy liquid is rapidly cooled by a rapid solidification method to form an amorphous alloy structure; Annealing the amorphous alloy structure, and controlling the temperature and time during the annealing process so that part of the amorphous alloy structure forms an amorphous nanocrystalline alloy structure; The amorphous nanocrystalline alloy structure is formed and processed, and then annealed to prepare a magnetic core of a desired shape and size.

2. The method for preparing amorphous nanocrystalline magnetic core of DBI type low voltage current transformer according to claim 1, characterized in that: A magnetic field is applied during the re-annealing process.

3. The method for preparing the amorphous nanocrystalline magnetic core of a DBI type low voltage current transformer according to claim 2, characterized in that: The applied magnetic field strength B is calculated as: Among them, B_s is the saturation magnetic induction intensity, H represents the intensity of the external magnetic field, and H_c represents the critical magnetic field of the material.

4. The method for preparing amorphous nanocrystalline magnetic core of DBI type low voltage current transformer according to claim 1, characterized in that: Before the annealing treatment is performed again, the surface of the magnetic core formed by the amorphous nanocrystalline alloy structure is plated.

5. The method for preparing amorphous nanocrystalline core of DBI type low voltage current transformer according to claim 1, characterized in that: The metal material is iron; the additives include silicon, cobalt and niobium; the mass fraction ratio of the metal material and the additives is: iron: 75%-80%; silicon: 10%-15%; cobalt: 5%-10%; Niobium: 1%-3%.

6. The method for preparing the amorphous nanocrystalline magnetic core of a DBI type low voltage current transformer according to claim 5, characterized in that: The additives also include: surfactants, stabilizers, fluxing agents, grain boundary strengtheners, and oxidants; The mass fraction of the surfactant is 0.1%-2%; the mass fraction of the stabilizer is 0.1%-5%; the mass fraction of the flux is 0.1%-2%; the mass fraction of the grain boundary strengthener is 0.1%-3%; and the mass fraction of the oxidant is 0.1%-1%.

7. The method for preparing amorphous nanocrystalline magnetic core of DBI type low voltage current transformer according to claim 1, characterized in that: The temperature during the annealing process is controlled within the range of 300° C. to 350° C., and the time during the annealing process is controlled within the range of 5 to 15 hours.

8. The method for preparing amorphous nanocrystalline magnetic core of DBI type low voltage current transformer according to claim 1, characterized in that: The formula for determining the annealing time is: Wherein, t is the annealing time, V is the volume of the amorphous nanocrystalline core, D is the thermal diffusion coefficient of the material, A is the surface area of ​​the material, E is the activation energy of the annealing process, R is the gas constant, T is the temperature, k, m, and n are empirical constants used to adjust the degree of influence of each term in the formula.

9. The method for preparing amorphous nanocrystalline magnetic core of DBI type low voltage current transformer according to claim 1, characterized in that: The formula for determining the annealing time is: Where T is the annealing temperature, V is the volume of the amorphous nanocrystalline core, E is the activation energy of the annealing process, K is the Boltzmann constant, and a, b, and p are empirical constants.

10. A magnetic core, characterized in that: The magnetic core is prepared by using the steps in the method for preparing an amorphous nanocrystalline magnetic core of a DBI type low-voltage current transformer as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Thermal conducting wire, thermal conducting wire preparation method and equipment

    CN121344446A